2004
DOI: 10.2172/1086353
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of Experimental Cetane Number Data

Abstract: In this report, we present a compilation of reported cetane numbers for pure chemical compounds. The compiled database contains cetane values for 299 pure compounds, including 156 hydrocarbons and 143 oxygenates. Cetane number is a relative ranking of fuels based on the amount of time between fuel injection and ignition. The cetane number is typically measured either in a combustion bomb or in a single-cylinder research engine. This report includes cetane values from several different measurement techniques -e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(146 citation statements)
references
References 5 publications
9
136
0
1
Order By: Relevance
“…However, the ring-opening of these compounds can lead to very large increases in cetane number. 9 The catalysis of the cracking of cyclohexane using acidic zeolites is therefore important. The cyclohexylium intermediates formed during the catalytic processes can undergo isomerization to methylcyclopentylium, a process that may facilitate ring-opening.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ring-opening of these compounds can lead to very large increases in cetane number. 9 The catalysis of the cracking of cyclohexane using acidic zeolites is therefore important. The cyclohexylium intermediates formed during the catalytic processes can undergo isomerization to methylcyclopentylium, a process that may facilitate ring-opening.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways can either be exploited in their native host or heterologously expressed in a genetically pliable microorganism (3). The physical and chemical properties of the resulting products are dependent on chain length and hydrophobicity; however, medium-chainlength (8-to 14-carbon) methyl esters, olefins, and alkanes exhibit many properties analogous to those of diesel and jet fuel and are therefore potential drop-in replacements (44,61).Several studies have demonstrated FFA overproduction in Escherichia coli (19,48,52,81,83). In each, the key strain modifications included overexpression of one or more cytosolic acyl-acyl carrier protein (ACP) thioesterases and deletion of fadD, or both fadD and fadE, which encode an acyl-coenzyme A (CoA) synthetase and acyl-CoA dehydrogenase, respectively.…”
mentioning
confidence: 99%
“…The database was built on the basis of experimental data gathered from different sources, such as the Design Institute for Physical Properties (DIPPR), database of chemical companies, the chemical database of the University of Akron (Ohio, USA) and the information available in Yaws' handbook [22][23][24][25][26][27]. It is important to notice the peculiarity of the CN database which was built on the basis of the compendium by Murphy et al [28] for oxygenated compounds and from Creton et al [29] for hydrocarbons. The local and complete database contains FP of 625 molecules, CN of 299 molecules, 5 634 experimental density values for 730 molecules and 3 547 experimental viscosity for 407 molecules.…”
Section: Methodsmentioning
confidence: 99%